2018
DOI: 10.1002/da.22782
|View full text |Cite
|
Sign up to set email alerts
|

Employment characteristics, work environment, and the course of depression over 23 years: Does employment help foster resilience?

Abstract: Background Depression is the leading cause of disability and represents a significant challenge to stable employment and professional success. Importantly, employment may also operate as a protective factor against more chronic courses of depression as it can function as a form of behavioral activation and scaffold recovery by facilitating community integration. The current study examined work-related characteristics as protective or risk factors for subsequent long-term depression trajectories. Methods Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…Within the general population, being employed has consistently been linked to better mental health and wellbeing [Backhans & Hemmingsson, 2012;Creed & Macintyre, 2001;Feather & O'Brien, 1986;Heinz et al, 2018;McKee-Ryan et al, 2005;Murphy & Athanasou, 1999;Paul & Moser, 2009;Voßemer et al, 2018;Wanberg, 2012], with greater benefits associated with higher levels of job satisfaction [Faragher et al, 2005]. As longterm outcomes in terms of mental health and well-being in employed adults with ASD is poorly understood, we monitored changes in mental health and well-being over time in newly employed adults with ASD, a population rarely represented in previous research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the general population, being employed has consistently been linked to better mental health and wellbeing [Backhans & Hemmingsson, 2012;Creed & Macintyre, 2001;Feather & O'Brien, 1986;Heinz et al, 2018;McKee-Ryan et al, 2005;Murphy & Athanasou, 1999;Paul & Moser, 2009;Voßemer et al, 2018;Wanberg, 2012], with greater benefits associated with higher levels of job satisfaction [Faragher et al, 2005]. As longterm outcomes in terms of mental health and well-being in employed adults with ASD is poorly understood, we monitored changes in mental health and well-being over time in newly employed adults with ASD, a population rarely represented in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with ASD, social support has been identified as a protective factor against depression and suicidal ideation [Hedley, Uljarević, Foley, et al, ; Hedley, Uljarević, Wilmot, Richdale, & Dissanayake, ], and is a significant predictor of state and trait anxiety [Harkry, ]. In non‐ASD populations, social support has been shown to predict life satisfaction [Strizović & Mratinković, ] and positive well‐being [Wilhelm et al, ], improves long‐term depression trajectories [Heinz et al, ], and provides a protective effect during crisis [Henderson, ]. In adults with physical disabilities, perceived quality of social support is associated with depression and anxiety (negatively) and positive well‐being (positively) [Tough, Siegrist, & Fekete, ].…”
Section: Predictors Of Mental Health and Well‐beingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study in the United States showed that working in an environment where professional status is high reduces depression and job stress [23]. Studies in Iran have shown that ignoring the professional status and social reputation of nurses is the cause of about 70% of their job dissatisfaction and unprofessional performance [18,20].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…In a study, people while self-assessing their health, showed that the better their occupational prestige, the better their health scores [8]. Also, research results in California showed that working in an environment full with a sufficiently occupational prestige would reduce depression and job stress [9]. Other studies in Iran have also shown that neglecting the occupational prestige and social status of nurses causes about 70% of job dissatisfaction and, consequently, their unprofessionally performance [2,3].…”
Section: Introductionmentioning
confidence: 99%